Strategi Pengelolaan Desa Wisata Serangan Dalam Mewujudkan Destinasi Wisata Yang Berkualitas - I Gede Putra Nugraha; Made Dian Putri Agustina (Widya Manajemen, 2021)
This article discusses the tourism village management strategy carried out by the Serangan Village Tourism Awareness Group in collaboration with the Denpasar City Government with local communities in developing quality tourist destinations in Serangan Village. The method used is observation and interviews with informants, namely the secretary of Serangan Pokdarwis, The Head of Serangan Village and Head of BUMDA Serangan. It is known that in the implementation of the development of tourist destinations in Serangan, the government and tourism awareness groups in Serangan Village take a role as a facilitator in preparing tourism facilities and infrastructure in Serangan and also as a dynamisator which provides skills training and governance of tourist villages so that the management of Serangan tourist destinations becomes more professional.